Cold‐stored leukoreduced CPDA‐1 whole blood: in vitro quality and hemostatic properties. Issue 5 (18th March 2020) - Sivertsen, Joar; Braathen, Hanne; Lunde, Turid Helen Felli; Kristoffersen, Einar K.; Hervig, Tor; Strandenes, Geir; Apelseth, Torunn O.
Abstract : BACKGROUND: Some jurisdictions require leukoreduction of cellular blood components. The only whole blood collection set with a platelet‐saving filter uses citrate‐phosphate‐dextrose (CPD) as storage solution. Substituting CPD with citrate‐phosphate‐dextrose‐adenine (CPDA‐1) increases shelf life from 21 to 35 days. This would simplify prehospital and rural resupply and reduce wastage. We investigated in vitro quality and hemostatic properties of CPDA‐1 whole blood leukoreduced with a platelet‐saving filter. STUDY DESIGN AND METHODS: CPDA‐1 whole blood was leukoreduced using a platelet‐saving filter and stored 35 days. EDQM requirements, hematology, metabolic parameters, thromboelastography, light transmission aggregometry, fibrinogen, factor VIII, and interleukin‐6 were measured on Days 0, 1, 14, 21, and 35 and compared to non‐leukoreduced blood. RESULTS: All units met EDQM requirements. Leukoreduction yielded residual white blood cell count <1 × 10 6 and 87% platelet recovery on Day 1. It caused reduction in thromboelastography parameters, but not aggregometry response. No hemolysis >0.8% was observed. Factor VIII was higher on Day 35 in the leukoreduced group, 37.9 (95% CI: 26.0, 49.8) versus 13.8 (9.4, 18.2) IU/dL. In both groups, aggregation was significantly reduced by Day 14. Thromboelastography showed remaining platelet activity on Day 35, MA 46.9 (42.1, 51.7) in the leukoreduced and 44.3 (39.6, 49.0) mm in the non‐leukoreduced group. Fibrinogen was within reference ranges at Day 35 (>2 g/dL). Interleukin‐6 was not detectable. CONCLUSION: Leukoreducing CPDA‐1 whole blood with a platelet‐saving filter did not compromise hemostatic properties. We encourage development of a single bag CPDA‐1 whole blood collection set with in‐line platelet‐saving filter.